EXPLORING TRANSNATIONAL UNDERSTANDINGS OF AGE-FRIENDLY CITIES AND COMMUNITIES. (16th November 2018) - Menezes, D; Woolrych, R; Makita, M; Sixsmith, J; Murray, M; Smith, H; Reddy, S; Duvvuru, J
Abstract: Ageing populations have generated new challenges in how to best design urban environments that support and promote everyday social engagement and healthy urban living for older people. In 2007 the World Health Organization published Age-friendly Cities: A Guide, which led to the development of interventions and policies at the city and community level aimed at supporting active ageing. Whilst existing urban interventions have addressed the physical and tangible aspects of the urban environment, the relational aspects of place (i.e. social engagement, place identity and attachment) have not been well articulated. This poster presents research being undertaken across two ESRC-funded projects bringing together research from Brazil, India and the UK to explore how older adults experience ageing across different urban, social and cultural contexts. The research reports on findings from qualitative data including semi-structured interviews, photo diaries and workshops already conducted in the UK and Brazil drawing upon themes of place belonging, social connectedness and respect. The poster concludes with an opportunity for examining the above themes in the context of India thus enabling cross-cultural experiential understandings of ageing-in-the-right-place which take into account transformations in both, person and place. This is important for developing age-friendly urban spaces that respond to different cultural, , social and political frameworks.